Public relations - Sonja Verwey Sonja Verwey (Communicare)
The advent of the Communication Age sets the challenge for public relations to lead corporations and other organisations on several levels, including the integration of relationships with various stakeholders, management functions, corporate and organisational structures as well as the integration with society. The successful integration at these levels will depend on the range of leadership that corporate communication professionals demonstrate from a macro level of interaction with society to a more micro level of individual stakeholders. As a result, public relations professionals must understand the major issues and trends confronting business and society, and be able to effectively communicate their longterm implications to management. Key issues t h a t w i l l remain of concern include many challenges that are a function of technology and changing times. The future of public relations practice depends on how well the profession adapts to changes in the new media environment and to shifts in economic, social and business paradigms. This article explores the reasons why public relations practice has grown increasingly complex and discusses the challenges, threats and opportunities facing the profession in the new millennium.